A Man of Many Devices. A 15 Year Old Boy with Exclusively Myocardial Mitochondrial Disease Received a LVAD, TAH, an Orthotopic Heart Transplant and ECMO in one Inpatient Episode. (July 2018) - Ragavan, Aaraby; Hannon, Vivienne; Walker, Christopher; Simon, Andre
Abstract : A 15 year old with mixed restrictive/dilated cardiomyopathy from myocardial mitochondrial disorder but normal skeletal muscle mitochondria, presented to a paediatric hospital with symptoms of cardiac failure in 2015. In March 2017 he decompensated despite medical therapy and a Multi-Disciplinary Team opted to insert a Heartware R (Heartware Inc, Framingham, USA) left ventricular assist device (LVAD) as a rescue bridge to transplant. Poor right ventricular (RV) function and developing tamponade led to poor LVAD flows and he was transferred to our unit in a state of collapse requiring significant vasopressor and inotropic support. The following day, the LVAD was exchanged for a Total Artificial Heart (TAH) (Syncardia Systems LLC, Tucson, USA). The LVAD inflow was found to have deviated into the septum, distorted by severe ventricular hypertrophy. He was listed for a super urgent heart transplant and transplanted 36 days later. His ICU recovery was complicated by prolonged RV failure and vasoplegia. This required 6 days of central veno-arterial extra-coporeal membrane oxygenation (VA ECMO). The sternum was open for 10 days and there were episodes of tamponade and bleeding with a persistent coagulopathy. Following successful ECMO explantation, he had bilateral pneumothoraces and a spontaneous pneumopericardium, which persisted radiologically for 14 days and was managed conservatively. He has been discharged to the ward for rehab of critical care weakness, but requires on-going renal replacement therapy, and has been hospitalised for 249 days at present. He went to the operating room on 10 occasions at this institute and received a total of 63 units of red cells, 22 platelet pools, 34 fresh frozen plasma and 10 courses of prothrombin complex concentrates. The Paediatric Interagency Registry for Mechanical Circulatory Support published in July 2017 reports 364 patients receiving 432 devices in 42 reporting hospitals in the USA. 1 80% received an LVAD and 2% a TAH. None converted a LVAD to TAH and then a transplanted heart. 22% of deaths were attributable to 'circulatory' causes and a further 26.6% from Multi-Organ Failure. The choice of device to bridge to transplant in this age group is still an evolving process, 2 made more difficult in cases of rescue therapy for acute decompensation. This unique case describes some of the challenges involved. References [1] Blume ED et al. "Second annual Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs) resport: Pre-implant characteristics and outcomes". J Heart Lung Transplant. 2017 Jul 4. Pii: S1053-2498(17). Doi:10.1016/j.healun.2017.06.017 [2] Kirk R et al. ISHLT Guidelines for the Management of Pediatric Heart Failure. International Society for Heart and Lung Transplantation. Bookbaby (pub). 2014